EPID-01. COMPARATIVE SURVIVAL ANALYSIS OF PEDIATRIC CENTRAL NERVOUS SYSTEM TUMORS BETWEEN BOSTON AND EGYPT. Issue 2 (22nd June 2018) - Auwarter, Emily; Shyr, Derek; Ma, Clement; Aziz, Amal Abdel; Maher, Islam; Haddad, Alaa El; Ibrahim, Ahmed; Beltagy, Mohamed El; Marcus, Karen; Zaghloul, Mohamed; Manley, Peter
Abstract: Pediatric brain tumors affect many children worldwide, attributing to 25% of all diagnosed pediatric cancers annually. More than 85% of those newly diagnosed pediatric brain tumor cases occur in developing, low-middle income countries (LMICs). There is paucity in overall survival studies that examine 5-year survival of children in LMICs compared to children in HICs. A retrospective chart review was conducted of 299 patients diagnosed with medulloblastoma or ependymoma, and treated at either Dana-Farber Cancer Institute (DFCI), Boston, MA or Children's Cancer Hospital Egypt (CCHE), Cairo, Egypt. The study cohort data was extracted from medical records and cancer registries from both hospitals identifying 225 cases from CCHE and 74 cases from DFCI. Patients diagnosed between 2007 to 2012, were abstracted and the follow up period of patients for outcomes took place through 2016. We evaluated demographic and clinical factors of overall survival (OS) using log-rank test and Kaplan-Meier curves stratified by tumor type. Overall survival rates were compared between the two cohorts with a median follow up of six years. Five-year OS for DFCI was 80 ± 6% (medulloblastoma) and 95 ± 5% (ependymoma), and for CCHE was 66 ± 4% (medulloblastoma) and 64 ± 6% (ependymoma). Type of treatment received was associated with significantly improved OS among medulloblastoma patients. With current treatment protocols, there is still upwards of 20% mortality with medulloblastoma and ependymoma. In LMICs these numbers are even higher. These findings highlight the importance of collaboration between developed countries and LMICs to consolidate therapies to improve overall survival.